Effects of Horizontal Acceleration on Human Visual Acuity and Stereopsis - Horng, Chi-Ting (Int J Environ Res Public Health, 2015)
The effect of horizontal acceleration on human visual acuity and stereopsis is demonstrated in this study. Twenty participants (mean age 22.6 years) were enrolled in the experiment. Acceleration from two different directions was performed at the Taiwan High-Speed Rail Laboratory. Gx and Gy (< and >0.1 g) were produced on an accelerating platform where the subjects stood. The visual acuity and stereopsis of the right eye were measured before and during the acceleration. Acceleration <0.1 g in the X- or Y-axis did not affect dynamic vision and stereopsis. Vision decreased (mean from 0.02 logMAR to 0.25 logMAR) and stereopsis declined significantly (mean from 40 s to 60.2 s of arc) when Gx > 0.1 g. Visual acuity worsened (mean from 0.02 logMAR to 0.19 logMAR) and poor stereopsis was noted (mean from 40 s to 50.2 s of arc) when Gy > 0.1 g. The effect of acceleration from the X-axis on the visual system was higher than that from the Y-axis. During acceleration, most subjects complained of ocular strain when reading. To our knowledge, this study is the first to report the exact levels of visual function loss during Gx and Gy.